Comparison of falls and cost-effectiveness of the group versus individually delivered Lifestyle-integrated Functional Exercise (LiFE) program: final results from the LiFE-is-LiFE non-inferiority trial - Jansen, Carl-Philipp; Gottschalk, Sophie; Nerz, Corinna; Labudek, Sarah; Kramer-Gmeiner, Franziska; Klenk, Jochen; Clemson, Lindy; Todd, Chris; Dams, Judith; König, Hans-Helmut; Becker, Clemens; Schwenk, Michael (Age & ageing, 2023)
Background: the individually delivered Lifestyle-integrated Functional Exercise (LiFE) was shown to improve physical activity (PA) and reduce fall incidence, however being rather resource-consuming due to one-to-one delivery. A potentially less resource-intensive group format (gLiFE) was developed and compared against the original program, considering higher risk of falling due to possible PA enhancement.
Gesehen am 03.05.2023